Quenching Greedy Souls in Metal Lakes: A Metallurgic Image in Thespesius’s Vision of the Afterlife (Plutarch, De sera num. 30, 567c-d) - Morrone, Daniele (ARYS. Antigüedad: Religiones y Sociedades, 2022)
Plutarch’s theological dialogue De sera numinis vindicta ends with an eschatological myth narrating the afterlife vision of Thespesius (22-33, 563b-568a), centred on the souls’ “purification” from their earthly vices – obtained by means of punishments – and on the process of their reincarnation. This myth includes symbolic images of metallurgic interest. The most elaborate of these corresponds to the description of the chastisement of the “insatiable” and “greedy” souls, which are cyclically immersed into lakes of gold, lead, and iron, enduring painful transformations in each lake (30, 567c-d). This article focuses on the analysis of the implications and literary genesis of this scene, in the frame of the rest of the myth and of the dialogic part of De sera num., of Plutarch’s ethical and scientific ideas, of his culture, and of the tendencies of his metaphorical and analogical prose (as evidenced by his other works). It begins with an introduction to Plutarch’s religious thought and use of Platonic myths, defending the assumption that these should be treated as non-literal “enigmatic” tales and thus interpreted symbolically. A section is then dedicated to the narrative frame of Thespesius’s vision – the story of the moral conversion of an unscrupulously hedonist and greedy man – and to Plutarch’s symbolic presentation of the stains of vice (26, 565b-d), each associated with a colour, focusing on the stain of “miserliness and greed”. After an overview of the other punishments witnessed by Thespesius, mainly to be interpreted as forms of contrapasso and exhibitions of the souls’ hidden, wicked selves, the analysis of Plutarch’s treatment of greed is completed with an extensive discussion of the scene of the metallic lakes. Previous scholarly treatments of the scene are also discussed, with a focus on those which connected it with alchemy. Considering a recently proposed comparison between Plutarch’s scene and some of the images used by the alchemist Zosimus in his allegorical dreams (MA X, XI, XII Mertens), the hypothesis of their affinity is explored with mainly negative results. However, a further hypothesis is suggested without full endorsement: namely, that the symbols used by Plutarch, like those used by Zosimus, were influenced by the aesthetics of Egyptian and/or Jewish religion in the syncretising environment of 1st-cent. CE Alexandria.
Keywords: afterlife; alchemy; Alexandria; colours; contrapasso; Delphi; Eschatology; ethics; gold; iron; iron quenching; lead; metallurgy; metaphors; platonic myth; Plutarch of Chaeronea; punishments; septuaginta; souls; symbols; Theology; vices; Zosimus of Panopolis